MENIMBANG KEKUATAN DAN KELEMAHAN HERMENEUTIKA SEBAGAI METODE INTERPRETASI TEKS-TEKS KEAGAMAAN - supangat fsh (UIN Walisongo Semarang, 2020)
The use of hermeneutics in understanding the Qur'an is confronted with controversies in disclosure, revolving around hermeneutic historicity, hermeneutic dissimilarities with interpretation, differences in the character of the Qur'an and the Bible, subjectivity and relativity of interpretation, reproduction of meaning and contextuality, not in detail, and not procedural. For groups who consider strengths and weaknesses in the interpretation of the Koran actually has the same purpose, namely to explain the purpose and message of the Qur'an as religious texts as a guide to human beings that is appropriate at every time and place. For those who are considered media interpreters of the Koran trying to elaborate the teachings of the Koran according to its context as a strength. Whereas those who consider hermeneutic weaknesses as a means of interpretation of religious texts feel obliged to apply the Qur'an in the lives of Muslims throughout time, which have been understood literally by the ulama and maintain the genuine and very established methods that have been formulated by Salafus shâlih namely interpretation and takwil methods that cannot be matched with hermeneutics. When accepting a new method, Muslims must be able to be wise to see strengths and weaknesses as a means of interpreting religious texts, not rejecting blindly and also not accepting as a whole, selective attitude is very necessary. Hermeneutics is accepted as a method of interpretation aimed at living the world of texts which nuances of the past with the empirical world today, so that it can answer all the problems that occur in the midst of society, by paying attention to the interpretation methods that have been formulated by scholars with compromise. Keywords: Hermeneutics, Religious texts, Accept and reject, compromise